Metode Yanbu’a dan Kemampuan Baca Tulis Al-Qur’an Siswa di SD Assalaam Kota Bandung - Syarief Ahmad, Khoirur Roji; Febri Liana Soleha; Mila Nur Laila; Muhamad Rizki Pajar; Hani Hadiati Pujawardani (Jurnal Dirosah Islamiyah, 2024)
This study aims to find out how learning the Qur'an using the Yanbu'a method at Assalaam Elementary School. This type of research uses a qualitative approach with descriptive methods in the nature of field research. Data collection techniques using observation, interviews and documentation. The results of this study indicate that: First, OPP curriculum learning (Progressive Personal Orientation) has a developmental speed of understanding the material, optimal development frees students from the limitations of learning seasons and develops optimally. Second, this learning is in collaboration with TPQ Assalam the teacher has more competence in the field of Al-Qur'an. Based on the results of this study, it can be seen that using the Yanbu'a method can improve the ability to read and write the Qur'an.